2019
DOI: 10.1371/journal.pone.0222959
|View full text |Cite
|
Sign up to set email alerts
|

Engagement in care among women and their infants lost to follow-up under Option B+ in eSwatini

Abstract: Background Universal antiretroviral treatment (ART) for pregnant women with HIV, Option B+, has been adopted widely for prevention of mother-to-child HIV transmission (PMTCT). Some evidence shows high loss to follow-up (LTF) under this model. However, gaps in data systems limit this evidence. We collected additional information for women and infants LTF from Option B+ in Eswatini to assess more accurate outcomes. Methods LTF at 6-months postpartum was assessed using facility data. Additional data was gathered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…Tracing studies in non-pregnant adults have reported higher rates of successful tracing, several with over 80% outcome ascertainment for the outreached population [ 21 , 30 , 31 ]. In eSwatini, community tracing of women who were LTFU ascertained outcomes in 44.7% of women [ 23 ], while in Malawi only 40% of women LTFU in Option B+ programs were successfully traced [ 24 ]. These low rates of outcome ascertainment highlight the challenges of community tracing of WLWHIV in SSA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tracing studies in non-pregnant adults have reported higher rates of successful tracing, several with over 80% outcome ascertainment for the outreached population [ 21 , 30 , 31 ]. In eSwatini, community tracing of women who were LTFU ascertained outcomes in 44.7% of women [ 23 ], while in Malawi only 40% of women LTFU in Option B+ programs were successfully traced [ 24 ]. These low rates of outcome ascertainment highlight the challenges of community tracing of WLWHIV in SSA.…”
Section: Discussionmentioning
confidence: 99%
“…Several tracing studies have addressed the outcomes of non-pregnant adults who have become LTFU [18][19][20][21]. However, other than three studies from Zimbabwe, eSwatini and Malawi, there is a dearth of knowledge about the outcomes of pregnant women initiating ART who subsequently become LTFU [22][23][24]. Such outcomes may include estimates of HIV viral suppression, MTCT and care status among women who disengage from HIV care programs.…”
Section: Introductionmentioning
confidence: 99%
“…More recent data after institution of Option B+, however, show low rates of viral suppression and high losses to follow-up: for example in eSwatini 53% postpartum retention in care [8], in Tanzania 39% viral suppression at 12 months postpartum [9]. Follow-up studies with tracing of women lost to specific clinic follow-up show that some women are in care elsewhere, though overall postpartum retention in care estimates remain sub-optimal [10]. For women retained in care, adherence to therapy remains a challenge.…”
Section: Introductionmentioning
confidence: 99%